Oil Cultures, World drama and contemporaneity: questions of time, space and form in Ella Hickson's Oil. Issue 11 (2nd November 2022) - Fakhrkonandeh, Alireza
ABSTRACT: Oil is unanimously recognised as the most vital, ubiquitous, yet paradoxically invisible, commodity of modern global economy and history. However, scant critical attention has hitherto been paid to the question of oil and oil culture in the context of contemporary Anglo-American drama. Ella Hickson's Oil is one of the first works that takes oil and its implications as its sustained focal point. This essay ponders and probes the epistemic, ethical, aesthetic and ontological facets of oil as they feature in Hickson's Oil . This essay is primarily concerned with the questions of dramatic form, petro-modern subjectivity, and history. Its crux is a demonstration of Hickson's Oil as a 'worlded' play, along with the manner Hickson depicts the age of oil to be capitalogenic – thereby presenting it to belong to a capitalocene rather than an Anthropocene. This task entails the exploration of the treatment of space(s) and time(s) in the play, along with their logic of connection. It also involves a scrutiny of the pivotal formal components and structural logic of Hickson's Oil . To effectively characterise the non-naturalistic features of the 'worlded form' in Oil, I will draw on a cluster of intertwined concepts, including allegory, petro-magic realism, Trauerspiel, and Uchronia.